Comparative Analysis of received GSM Signal Strength Network in University of Maiduguri, Borno State, Nigeria - Adegoke, A. O.; Bakura, M. U. M.; Mustapha, I.; Sani, I. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
GSM Network in Nigeria in recent times has been epileptic due to drop in signal strength, which causes customer dissatisfaction with the quality of service delivery by network operators. University of Maiduguri has experience low signal quality in recent years due to frequent dropped calls, poor network interconnectivity, echoes and network congestion, therefore this work presents a detail analysis of the received GSM signal strength in university of Maiduguri. An android application program known as network cell info Lite was used for the measurement of signal strength for three different network in the university at random sampling points. The three network considered are: Network A, Network B and Network C, in three different locations; Academic area, student hostel and staff quarters within the university. The data collected were analyzed using SPSS Statistical tool. The mean value of the signal strength received using the software application shows that Network A with HSPA -91.91dB and GPRS -73.59Db is the best network in the academic area, Network B with HSPA -87.27dB and GPRS -73.43dB has the best network quality in the staff quarters and Network C with HSPA -88.73dB and GPRS -69.85dB is the best network in the student hostel, results above shows that the quality of signal strength depends on location within the university.